2009
DOI: 10.1186/1743-422x-6-198
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a novel gene associated with human influenza A viruses

Abstract: BackgroundInfluenza A virus genomes are comprised of 8 negative strand single-stranded RNA segments and are thought to encode 11 proteins, which are all translated from mRNAs complementary to the genomic strands. Although human, swine and avian influenza A viruses are very similar, cross-species infections are usually limited. However, antigenic differences are considerable and when viruses become established in a different host or if novel viruses are created by re-assortment devastating pandemics may arise.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 79 publications
0
15
0
3
Order By: Relevance
“…[4]. В настоящее время экспрессия гена NSP при репликации вируса ещё не установлена [6][7][8][9]. Пока не известно, каким образом и в клетках каких тканей может синтезироваться белок NSP вирусов гриппа A. Однако в процессе его синтеза в целостном организме может формироваться гуморальный и/или клеточный иммунный ответ на данный вирусный белок.…”
Section: биохимия биофизика молекулярная биологияunclassified
“…[4]. В настоящее время экспрессия гена NSP при репликации вируса ещё не установлена [6][7][8][9]. Пока не известно, каким образом и в клетках каких тканей может синтезироваться белок NSP вирусов гриппа A. Однако в процессе его синтеза в целостном организме может формироваться гуморальный и/или клеточный иммунный ответ на данный вирусный белок.…”
Section: биохимия биофизика молекулярная биологияunclassified
“…These results confirm that the vRNA of segment 8 of human influenza A virus has a messenger translation function that is in accordance with the concept of bipolar (ambisense) influenza A viral genome strategy. Currently, the significance of the detected gene and the possibility of NSP protein expression during virus replication have not yet been established [9][10][11][12]. The importance of the positivepolar gene in the influenza A virus has been proved by the fact that, since the beginning of the 20th century until the present time, this gene remains fully functional in the genome of human viral strains despite the pronounced drift variability of the viral genome [6].…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to vaccine strain A/California/07/2009 [ Table 2 Analysis of all the selected HA proteins with multiple software tools including SignalP v3.0, Phobius, SPOCTOPUS and Signal-BLAST [15] showed that the N terminal of the HA protein as having a signal peptide which consists of about 17 amino acids and the cleavage site present between positions 17 and 18. HA is cleaved into a signal peptide when mature proteins are produced.…”
Section: Introductionmentioning
confidence: 99%